Clinical survey for registering treatment decision criteria in advanced non-small-cell lung cancer radiotherapy and determination of the dose–response relationship for 1-year survival. Issue 1 (22nd April 2013) - Chalimou, Ioanna; Lind, Helena; Sakellaropoulos, Georgios C.; Lind, Bengt K.; Papanikolaou, Nikos; Nikiforidis, Georgios C.; Mavroidis, Panayiotis
Abstract: Purpose: Recent studies have suggested significant variations in radiotherapy schedules used to treat advanced non-small-cell lung cancer (NSCLC), both between different centers in one country as well as between countries. In this study, different treatment methodologies have been explored using management plans proposed by radiation oncologists regarding general questions and theoretical case histories for patients with advanced NSCLC. Materials and methods: The survey was conducted by sending a questionnaire to 24 radiotherapy centers in Europe. The questionnaire was composed of two sections. The first section concerned reasons for giving radiotherapy, parameters that influence the choice of total dose and fractionation for radiotherapy and kind of equipment used. The second section concerned the management of five theoretical patients (A–E) regarding the selection of the radiotherapy technique and the aim of treatment (radical or palliative). Furthermore, 19 trials comparing different regimens of palliative radiotherapy in patients with NSCLC were reviewed. There were marked differences in the doses of the investigated radiotherapy schemes, the patient characteristics and the assessed outcome measures. Results: 70% of the responders answered that the most important factors for deciding what dose and fractionation scheme to use were: metastases, performance status (PS) of the patient, lung function and size of the primary tumour. The most common reasons for giving the treatment were symptom relief, prolongation of life and, in some cases, possibly cure. More than 95% of the responders stated that they would give radiotherapy in each of these cases. The total doses proposed where 20 Gy in five fractions or 30 Gy in ten fractions in 2 weeks for the cases A and D. If the previous two schemes were converted to a fractionation scheme delivering 2 Gy per fraction, the equivalent doses would be 23 and 33 Gy, respectively. For the cases B, C and E, the proposed fractionation schemes were 2 Gy daily to 60–68 Gy in 6 weeks or 2 Gy daily to 68 Gy in 7 weeks. For the case E, 20% of the responders suggested Stereotactic Body Radiotherapy (SBRT) giving 21 Gy three times a week with a day apart to 63 Gy. The total dose and number of fractions of radiotherapy are related to the perceived aims and expectations of treatment. Those aiming at extending life would give significantly higher total doses in a larger number of fractions, whereas those aiming at relieving symptoms would give significantly lower total doses. There is evidence for an increase in survival, in patients who are given higher radiotherapy doses, especially in those patients with better PS. Conclusions: This survey demonstrates a range of treatment strategies for advanced and inoperable NSCLC within Europe. There are a number of factors that influence the perceived aims of treatment and treatment planning. These factors should be taken into account when evaluating the effectiveness of different irradiation techniques, especially in the determination of radiobiological parameters and dose–response relations. The majority of patients should be treated with short courses of palliative radiotherapy, of one or two fractions. The use of high-dose palliative regimens using many fractions or SBRT should be considered for selected patients with good PS.